Interventions to Prevent Chronic Energy Deficiency in Women of Reproductive Age - Pujiastutik, Yanuar Eka; Apriyanto, Bagus Sholeh; Wahyuni, Sri; Yauri, Indriani; Cholis, Eko Prasetyo (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Women of childbearing age (WUS) belong to a vulnerable group whose health status must be considered, especially their nutritional status. Ignorance about nutritious food can lead to high cases of KEK in WUS. The provision of health education is expected to increase knowledge in WUS so as to increase efforts to prevent KEK early and can reduce the incidence of KEK, especially during pregnancy and the First 1000 Days of Life (HPK). This study aims to analyze the effect of health education on the level of knowledge of WUS about the prevention of KEK. This study used PreExperimental method with one group pre-test post-test design. The sampling technique used in this study was total sampling with a population of 42 WUS in Surat Village. This study was analyzed using the Wilcoxon Signed Rank Test. The results of this study indicate that there is an increase in knowledge value with an average value of each respondent as much as 29% after the provision of health education on the prevention of KEK with the significance value of the Wilcoxon test is 0.000 which means that the significance value is less than the ρ-value (sig <0.05).